(untitled) (Fiep Bulletin - online, 2014)
This research investigated the possibility of offering knowledge about swimming, as the content of the physical education classes the final years of primary school, students from schools that do not have adequate physical infrastructure (pool) for this practice, analyzing their performance, before and after the provision of these activities in the liquid medium (pool) outside the school environment. The theoretical approaches to learning to swim, showing a brief historical overview and some of the benefits of this practice, still discoursing on the main features of the freestyle (or crawl), emphasizing the adaptation to the water, your body position in the water, breathing, coordination and movement of the upper and lower thrust arm and leg propulsion. This research is characterized as quantitative descriptive and exploratory objective, character pre-experimental method and application study, and was conducted with eight students at the School Vergínio Cerutti in Frederico Westphalen, which do not have classes swimming as content of Physical Education. The research process was conducted in four stages: preliminary observation of student performance, implementation of lesson plans, further observation of student performance and comparison of results obtained in the first step with the records made in the second stage. The final thoughts indicated that swimming can be taught in a school environment, even if the school does not have adequate physical infrastructure (swimming), through the preparation of lesson plans and structured to enable the teaching of some aspects of swimming in space school, providing opportunities for students to access the knowledge of the sport of swimming and awakening the taste for the practice of this activity, which is beneficial to health.